Activity of Homocarnosine and Other Compounds Against Staphylococcal Infections in Mice - Tanaka, Kinji (1968)
Homocarnosine and carnosine have been identified in bovine brain extracts which are effective in protecting mice against infections by Staphylococcus aureus. These peptides, as well as l-1-methylhistidine, β-alanine, γ-aminobutyric acid, δ-aminovaleric acid, ε-aminocaproic acid, 1-aminomethylcyclohexane-4-carboxylic acid, and anserine, were tested as prophylactic agents against S. aureus infections in C3H and Swiss mice. Histidine and methylhistidine were ineffective in preventing mortality in both mouse strains. Carnosine, anserine, and ε-aminocaproic acid were effective in C3H but not in Swiss mice. β-Alanine and γ-aminobutyric acid were weakly effective (C3H) or ineffective (Swiss). δ-Aminovaleric and 1-aminomethylcyclohexane-4-carboxylic acid (tested only in Swiss) were somewhat effective in early stages of the infection. Homocarnosine was the best compound and was highly effective in protecting both mouse strains against S. aureus infections by the testing procedure employed.